Kedudukan Hukum Transaksi Jual Beli Tanah Bersertifikat Hak Milik Yang Diblokir Oleh Badan Pertanahan Nasional - Teikuar, Yatno Krisando; Uktolseja, Novyta; Radjawane, Pieter (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2024)
Land ownership rights are marked by a certificate issued by the National Land Agency (BPN), which has strong evidentiary power regarding physical and legal data of the land. This certificate is the initial evidence that can be used by the owner to strengthen his claim of ownership rights to the land. However, this certificate can be blocked by the BPN when there are legal problems, such as demands or claims from other parties, which require the delay of the transfer of rights process until there is a legal settlement. This study aims to examine the legal status of land sale and purchase transactions with land title certificates that are blocked by the BPN and to understand the legal consequences of these transactions. The method used in this study is normative juridical with a literature study approach or secondary data to analyze various relevant regulations and literature. The results of the study show that land sale and purchase transactions with land title certificates but blocked by the BPN are not legally valid. This blockage indicates that there is a dispute or unresolved legal problem on the land, so that all forms of transfer of rights cannot be carried out legally until the block is lifted. As a result, this transaction causes a violation of the law for the parties involved, where the seller cannot transfer his ownership rights, and the buyer is at risk of not obtaining legally recognized ownership rights. On the other hand, transactions that are still carried out on blocked land can end in further legal defense, including a lawsuit for breach of contract from the buyer because the transaction is considered invalid.